Implementing interdisciplinary methods in the educational framework - Sukhomlynova, Olena; Lysenko, Tetiana; Rembach, Olha; Pavelko, Viktoriia; Kovalchuk, Yurii (Cadernos de Educação, Tecnologia e Sociedade, 2024)
The article aims to study the principles and ways of implementing the interdisciplinary approach into the educational process. The research is based on empirical experience in teaching at higher education institutions, an analysis of educational programmes of higher educational institutions in Ukraine, a survey of medical university lecturers, as well as a pedagogical experiment on the effectiveness of the interdisciplinary approach conducted at Ivano-Frankivsk National Medical University among second-year students of the Dentistry programme. The control group studied two separate subjects, “Foreign (English) Language for Professional Purposes” and “Social Medicine, Public Health, and the Fundamentals of Evidence-Based Medicine”, while the experimental group took an integrated course, Module 1, which combined these two subjects in the form of binary lessons. The integrated course had the most significant impact on forming sufficient and high levels of knowledge, with a difference of 9% and 7%, respectively, between the control and experimental groups. Additionally, the experimental group had 10% fewer students with low-developed skills and abilities. The experiment data confirm the considerable effectiveness of integrated courses, suggesting that universities should actively introduce them into the educational process. The authors propose the following ways to implement the interdisciplinary approach: inclusion of interdisciplinary topics in lectures; conducting binary lectures; integrating common cases into seminar and practical disciplines to solve interdisciplinary practical tasks and other modern educational technologies of problem-based learning; developing interdisciplinary courses for elective and optional subjects; preparing articles and conference presentations with two or more co-authors from related fields of knowledge. Based on the empirical method, it was established that the effectiveness of applying the interdisciplinary approach in higher education is associated with the systematisation and structuring of acquired specialised knowledge, stimulation of student motivation, and scientific inquiry. O artigo tem como objetivo estudar os princípios e as formas de implementar a abordagem interdisciplinar no processo educativo. A investigação baseia-se na experiência empírica de ensino em instituições de ensino superior, numa análise dos programas educativos de instituições de ensino superior na Ucrânia, num inquérito a professores universitários de medicina, bem como numa experiência pedagógica sobre a eficácia da abordagem interdisciplinar realizada na Universidade Nacional de Medicina de Ivano-Frankivsk entre estudantes do segundo ano do curso de Medicina Dentária. O grupo de controlo estudou duas disciplinas separadas, “Língua Estrangeira (Inglês) para Fins Profissionais” e “Medicina Social, Saúde Pública e os Fundamentos da Medicina Baseada em Evidências”, enquanto o grupo experimental frequentou um curso integrado, o Módulo 1, que combinava estas duas disciplinas sob a forma de aulas binárias. O curso integrado teve o impacto mais significativo na formação de níveis de conhecimento suficientes e elevados, com uma diferença de 9% e 7%, respetivamente, entre os grupos de controlo e experimental. Além disso, o grupo experimental teve menos 10% de alunos com competências e capacidades pouco desenvolvidas. Os dados da experiência confirmam a eficácia considerável dos cursos integrados, sugerindo que as universidades devem introduzi-los ativamente no processo educativo. Os autores propõem as seguintes formas de implementar a abordagem interdisciplinar: inclusão de tópicos interdisciplinares em palestras; realização de palestras binárias; integração de casos comuns em seminários e disciplinas práticas para resolver tarefas práticas interdisciplinares e outras tecnologias educativas modernas de aprendizagem baseada em problemas; desenvolvimento de cursos interdisciplinares para disciplinas electivas e opcionais; preparação de artigos e apresentações em conferências com dois ou mais co-autores de áreas de conhecimento relacionadas. Com base no método empírico, foi estabelecido que a eficácia da aplicação da abordagem interdisciplinar no ensino superior está associada à sistematização e estruturação dos conhecimentos especializados adquiridos, ao estímulo da motivação dos estudantes e à investigação científica.